Interpersonal regulation of learning and motivation : methodological advances - Vauras, Marja, 1953-; Volet, Simone (New York, NY : Routledge, 2013)
'Interpersonal Regulation of Learning and Motivation is the first book in the field to focus on major methodological advances in research on interpersonal regulation and motivation in learning. Interest in developing ways of capturing the dynamics of interpersonal regulation of learning and motivation in real-life activities is growing rapidly. Understanding the dynamics of learning and motivation in groups is particularly timely given the increased use of collaborative learning activities in schools and university settings, as well as through face-to-face and computer supported collaborative learning (CSCL) environments. While groups and collections of individuals in social interaction are expected to bring their own motivations and goals to the learning situations, it is also assumed that these are further shaped through interaction, as the group activity evolves. Research methodology publications in the field of learning, regulation and motivation are still dominated by a focus on the individual. The study of collaborative learning at both conceptual and methodological level has not incorporated the significance of social regulatory processes of learning and motivation. This is a new development in the field and one covered by this book. Areas covered include: - Meta-cognition and collaborative learning - Self and co-regulation - Teacher-Student interaction - Interpersonal learning and achievement - Motivation, identity and learning Interpersonal Regulation of Learning and Motivation brings together the work of scholars who have been studying interpersonal regulation of learning and motivation at the boundaries of the individual and the social, and who have made original methodological contributions to the study of interactive learning environments'--
Includes bibliographical references and index.
Keywords: Interaction analysis in education; Learning, Psychology of; Motivation in education; Interpersonal relations in children